TIMBER BOOM IN EAST KALIMANTAN (1967–1971): ECONOMIC GROWTH AND ENVIRONMENTAL IMPACT - Marfuah, Siti; Azmi, Muhammad (International Conference On Social Science Education, 2024)
Between 1967 and 1971, East Kalimantan witnessed a rapid increase in timber exploitation, commonly known as the "timber boom." This period of extensive deforestation was driven by Foreign Investment Law No. 1 of 1967, which attracted foreign investors through tax incentives and investment guarantees. The law enabled large-scale logging concessions, resulting in significant economic growth and triggering a massive wave of migration. Thousands of workers, primarily from Java and Sulawesi, relocated to East Kalimantan in search of employment in the logging industry and related sectors. This influx of migrants, along with the government's transmigration program, reshaped the region’s demographic and social landscape, intensifying competition for land and resources. This study employs historical methods to analyze the socio-economic and environmental consequences of the timber boom. It draws on primary and secondary sources, including government reports, logging concession data, archival records, and interpretations of the broader implications of forest exploitation. The findings indicate that while the timber boom generated short-term economic gains, it also led to widespread deforestation, biodiversity loss, and the disruption of traditional livelihoods. The absence of sustainable forest management practices resulted in long-term environmental degradation, leaving a lasting impact on the region's ecosystem.